2019
DOI: 10.1021/jacs.9b04729
|View full text |Cite
|
Sign up to set email alerts
|

How Metal Ion Lewis Acidity and Steric Properties Influence the Barrier to Dioxygen Binding, Peroxo O–O Bond Cleavage, and Reactivity

Abstract: Herein we quantitatively investigate how metal ion Lewis acidity and steric properties influence the kinetics and thermodynamics of dioxygen binding versus release from structurally analogous Mn–O2 complexes, as well as the barrier to Mn peroxo O–O bond cleavage, and the reactivity of Mn oxo intermediates. Previously we demonstrated that the steric and electronic properties of MnIII–OOR complexes containing N-heterocyclic (NAr) ligand scaffolds can have a dramatic influence on alkylperoxo O–O bond lengths and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 64 publications
(141 reference statements)
1
6
0
Order By: Relevance
“…These recent studies suggest that there is a continuing benefit to the study of the molecular electrocatalytic reduction of O 2 . The mechanistic fundamentals of homogeneous O 2 activation have relevance to the understanding of biological systems, as well as the development of better ORR and aerobic oxidation catalysts. , There is sustained interest in running the latter electrochemically, given the obvious parallels to the function of Cytochrome P450, which catalyzes the oxygenation of endogenous and exogenous molecules to produce important metabolites. Mechanistic and thermodynamic understanding of molecular catalysis can be the basis of intriguing systems with careful experimental design: a recent study combined Rh porphyrins with methane and O 2 to assemble an abiotic system capable of activity analogous to methane monooxygenase by exploiting electrochemically generated reaction gradients created by inorganic nanomaterials .…”
Section: Discussionmentioning
confidence: 99%
“…These recent studies suggest that there is a continuing benefit to the study of the molecular electrocatalytic reduction of O 2 . The mechanistic fundamentals of homogeneous O 2 activation have relevance to the understanding of biological systems, as well as the development of better ORR and aerobic oxidation catalysts. , There is sustained interest in running the latter electrochemically, given the obvious parallels to the function of Cytochrome P450, which catalyzes the oxygenation of endogenous and exogenous molecules to produce important metabolites. Mechanistic and thermodynamic understanding of molecular catalysis can be the basis of intriguing systems with careful experimental design: a recent study combined Rh porphyrins with methane and O 2 to assemble an abiotic system capable of activity analogous to methane monooxygenase by exploiting electrochemically generated reaction gradients created by inorganic nanomaterials .…”
Section: Discussionmentioning
confidence: 99%
“…We note that the stoichiometric chemistry of Mn complexes with thiolate containing ligands and O 2 has been explored extensively by Kovacs and coworkers. [71][72][73][74][75] Upon exposure to dry air, both centers were oxidized by a single electron and a bridging hydroxide species was recovered. Mechanistic studies established that the dinuclear monothiol species united two separate reaction cycles, where either H 2 O 2 or H 2 O production was favored.…”
Section: Catalytic O 2 Reduction Mediated By Mnmentioning
confidence: 99%
“…13D and F). 74,122 6. Critical analysis of homogeneous ORR by molecular Mn/Fe/Co Extensive studies on the ORR mediated by metalloporphyrins allows for a critical comparison of activity and mechanism for structurally analogous systems containing Fe, Co and Mn active sites.…”
Section: àmentioning
confidence: 99%
“…Much of our understanding of the properties of heme and nonheme iron enzyme dioxygen intermediates such as Fe­(III)–superoxos, Fe­(III)–peroxos, and high-valent iron oxos comes from small-molecule chemistry. Only a small number of these are derived from O 2 , , and despite the key role of thiolates in a wide variety of nonheme iron enzymes, only a small number of these contain thiolates in the coordination sphere. ,,, Key properties unique to aliphatic thiolate (RS – or Cys-S – ) ligands include an increase in the potency of high-valent iron oxo intermediates and, as shown by our group, the potency of iron-superoxo compounds with respect to their ability to cleave strong C–H bonds. , We also recently showed that aliphatic thiolates help to promote peroxo O–O bond cleavage. , Very few well-characterized iron-superoxo compounds have been reported, , and of those reported, only two incorporate a thiolate in the coordination sphere , and only one cleaves strong C–H bonds . We recently showed that aliphatic thiolate-ligated [Fe II (S 2 Me2 N 3 (Pr,Pr))] ( 1 ) reacts with O 2 (Scheme ) to form an unprecedented example of an aliphatic thiolate-ligated iron superoxo intermediate, [Fe III (S 2 Me2 N 3 (Pr,Pr))­(O 2 )] ( 2 ), which is capable of cleaving strong C–H bonds (e.g., tetrahydrofuran (THF) (BDE­(C–H) = 92 kcal mol –1 )) at −73 °C with a k H / k D = 4.8 .…”
Section: Introductionmentioning
confidence: 99%